Evaluation of open bite closure using clear aligners: a retrospective study - Kayla Harris; Kenji Ojima; Chisato Dan; Madhur Upadhyay; Abdulrahman Alshehri; Chia-Ling Kuo; Jinjian Mu; Flavio Uribe; Ravindra Nanda (SpringerOpen, 2020)
Abstract Objectives To evaluate the dental and skeletal effects that occur in the correction of anterior open bite with clear aligners. Materials and method In this single-center retrospective study, the mechanism of anterior open bite closure using clear aligners (Invisalign, Align Technology, Santa Clara, CA, USA) was evaluated by cephalometric superimposition based on records of patients consecutively treated by a single, experienced Invisalign provider. Inclusion criteria consisted of anterior open bite (overbite < 0.5 mm), adult patients (18+) at the beginning of treatment, consecutive records, and good quality pre- and post-treatment records, where the required landmarks were clearly visible. Results A total of 45 patients were included for data analysis with a mean age of 30.73 ± 8.0 years and initial open bite of − 1.21 ± 1.15 mm. During treatment, the upper incisors showed significant (p < 0.05) retraction [U1-SN'(°) = − 10.91 ± 6.95°], [U1-SN'perp(mm) = − 2.57 ± 1.75 mm] and extrusion [U1-SN'(mm) = 1.45 ± 0.89 mm]. The lower incisors also showed significant retraction [IMPA(°) = − 3.73 ± 4.91°), (ΔL1-MP'perp (mm) = − 1.08 ± 1.59] and extrusion (ΔL1-MP'(mm) = 0.53 ± 0.74). Regarding molar position, no significant changes were noted in the anteroposterior position of the upper [ΔU6-SN'perp(mm) = 0.01 ± 1.08 mm] and lower molar [ΔL6-MP'perp(mm) = 0.03 ± 0.87 mm]; however, there was a statistically significant intrusion of the upper [ΔU6-SN'(mm) = − 0.47 ± 0.59 mm] and lower molar [ΔL6-MP'(mm) = − 0.39 ± 0.76 mm]. Conclusion Open bite closure with clear aligners occurred due to a combination of maxillary and mandibular incisor extrusion and maxillary and mandibular molar intrusion, with slight mandibular auto rotation. Significant retraction of maxillary and mandibular incisors was also observed with treatment. Clear aligners are effective in reducing/controlling the vertical dimension in open bite patients.